High-sensitivity C-reactive protein and long term reperfusion success of primary percutaneous intervention in ST-elevation myocardial infarction. (1st December 2017) - Groot, Hilde E.; Karper, Jacco C.; Lipsic, Erik; van Veldhuisen, Dirk J.; van der Horst, Iwan C.C.; van der Harst, Pim
Abstract: Aims: In STEMI patients, success of reperfusion of primary PCI predicts cardiac remodeling and clinical outcome. This success may depend on inflammation. We aimed to investigate the association between inflammation and reperfusion success, left ventricular function and long-term mortality in STEMI patients. Methods: In 376 consecutive STEMI patients of the GIPS-III trial hs-CRP levels were measured at baseline, 2 weeks, 7 weeks and 4 months post-PCI. Myocardial blush grade was used to determine success of myocardial reperfusion. In multivariate models sex, age, hs-CRP levels at baseline, NT-proBNP levels at baseline, ischemia time, heart rate, TIMI flow, and CK, CKMB and troponin AUC were included. Follow-up was complete until 4 months. Results: Baseline hs-CRP levels were 2.1 mg/l (IQR 0.5–4.2 mg/l). hs-CRP levels were associated with impaired reperfusion (OR 1.239, 95% CI 1.006–1.527) and remained higher compared to patients with normal reperfusion up to 2 months after PCI (hs-CRP 1.9 mg/l (IQR 0.9–3.7 mg/l) versus 1.5 mg/l (IQR 0.7–2.7 mg/l), p = 0.041). In multivariate analysis baseline hs-CRP levels remained independently associated with impaired reperfusion. In patients with impaired reperfusion, hs-CRP and NT-proBNP levels remained higher during 4 months of follow-up. No correlation was observed between hs-CRP at baseline and left ventricular function at 4 months. The number of events was small and we observed no differences in mortality. Conclusion: Increased hs-CRP levels at presentation are associated with impaired microvascular reperfusion after PCI in STEMI patients and remain higher until 2 months follow-up.